Natural variations of BrHISN2 provide a genetic basis for growth‐flavour trade‐off in different Brassica rapa subspecies. Issue 6 (16th August 2021) - Su, Tongbing; Wang, Weihong; Li, Peirong; Xin, Xiaoyun; Yu, Yangjun; Zhao, Xiuyun; Zhang, Deshuang; Yu, Shuancang; Zhang, Fenglan
Summary: Selection for yield during B .  rapa breeding may have unintended consequences for other traits, such as flavour. LYH‐type (light yellow head) Chinese cabbage ( Brassica rapa ssp. pekinensis ) and wucai ( Brassica rapa L. ssp. chinensis var. rosularis ) varieties are becoming popular because of their unique flavour and yellow leaves. However, the molecular mechanism underlying the interplay for these traits remains unknown. We conducted a fine mapping and genome‐wide exploration analysis of the leaf yellowing of LYH and wucai, including transgenic plants, to identify causal genes. We identified that BrHISN2, a rate‐limiting enzyme in histidine biosynthesis, causes leaf yellowing by destroying LYH chloroplasts. Normal growing Brhisn2 mutant plants became etiolated and senesced at the cotyledon‐seedling stage. Sequence variations in the promoter confers cold‐dependent expression on BrHISN2, probably resulting in leaf yellowing in LYH and wucai. Insertions of two DRE cis elements and the subsequent recruitment of two CBF2 proteins by the DREs to the promoter provided the cold‐induced expression plasticity of BrHISN2 in plants. Both LYH and wucai are farmed in the fall, in which the temperature gradually decreases, therefore the CBF2‐ BrHISN2 module probably maximises the benefits of gene–environment interaction for breeding. We determined the mechanistic connections of chlorophyll synthesis and the growth‐flavour trade‐off in these B .  rapa varieties.